Prevalensi dan Derajat Infeksi Helminthiasis Gastrointestinal pada Sapi Bali (Bos sondaicus) di Peternakan Rakyat Mutu Desa Sepayung Kecamatan Plampang Kabupaten Sumbawa Besar Nusa Tenggara Barat - Ariandoko, Ariandoko; Kholik, Kholik; Atma, Candra Dwi; Ningytas, Novarina Sulsia Ista’In (Mandalika Veterinary Journal, 2021)
Bali cattle is one of the cattle that are more in demand by the community, especially the people of Sumbawa Besar. Healthy cows that are in a state or physiological body functioning normally, which means that cattle avoid various diseases, especially Helminthiasis. The purpose of this study was to determine the prevalence and degree of gastrointestinal helminthiasis infection in Balinese cattle (Bos sondaicus) in Mutu People’s Farms in Sepayung village, Plampang sub-district, Sumbawa Besar district, NTB. This research is a descriptive study with Based on Rates or calculation of the prevalence rate and degree of Gastrointestinal Helminthiasis infection in bali cattle feces at Mutu People’s Farm in Sepayung Village, Plampang District, Sumbawa Besar Regency, West Nusa Tenggara. This research was conducted in February 2020 in the Laboratory of the Faculty of Veterinary Medicine, West Nusa Tenggara University, examined using the Mc Master method and counted the number of worm eggs per gram of feces. Based on the results of laboratory tests conducted on 37 bali cattle feces samples, found 6 samples infected with Trichostrongylus sp. and 2 samples were infected with Ostertagia sp. The results of examinations that have been done, the prevalence found in this study is Trychostrongylus 16.21% while in Ostertagia it is 5.40% with the degree of infection in Trichostrongylus moderate infections and in mild infections Ostertagia. Based on the results of laboratory tests conducted on 37 bali cattle feces samples, found 6 samples infected with Trichostrongylus sp. and 2 samples were infected with Ostertagia sp. The results of examinations that have been done, the prevalence found in this study is Trychostrongylus 16.21% while in Ostertagia it is 5.40% with the degree of infection in Trichostrongylus moderate infections and in mild infections Ostertagia. Based on the results of laboratory tests conducted on 37 bali cattle feces samples, found 6 samples infected with Trichostrongylus sp. and 2 samples were infected with Ostertagia sp. The results of examinations that have been done, the prevalence found in this study is Trychostrongylus 16.21% while in Ostertagia it is 5.40% with the degree of infection in Trichostrongylus moderate infections and in mild infections Ostertagia.